HUBUNGAN ANTARA PENGETAHUAN MATEMATIKA DASAR DAN KEMAMPUAN SPASIAL DALAM MEMBACA PETA MAHASISWA PGSD PADA MATA KULIAH PENDIDIKAN IPS DI SD - Hatibu, Hardiyanti; A. Muhajir Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the relationship between basic mathematical knowledge and spatial ability in map reading among students of the Elementary School Teacher Education (PGSD) program enrolled in the Social Studies Education course. The research is grounded in the importance of integrative learning in teacher education, where students are expected to connect cross-disciplinary concepts, particularly between mathematics and social studies. Mastery of mathematical concepts such as scale, distance, and coordinate systems is assumed to be closely related to spatial skills in interpreting map representations. This study employed a quantitative approach with a correlational research design. The population consisted of 434 PGSD students from the Faculty of Education, Universitas Negeri Makassar, with a minimum sample of 81 students determined using the Slovin formula at a 10% margin of error. Data were collected through multiple-choice objective tests measuring basic mathematical knowledge and spatial map-reading ability. Data analysis was conducted using the Spearman Rank correlation (ρ) due to non-normal data distribution. The results revealed a positive and significant relationship between basic mathematical knowledge and spatial map-reading ability among PGSD students (ρ = 0.556; p < 0.001; effect size = 0.627). These findings indicate that mastery of basic mathematical concepts contributes to enhancing students’ spatial ability in reading and interpreting maps. Therefore, this study highlights the importance of adopting an integrative learning approach between mathematics and social studies to strengthen the numerical and spatial literacy of future elementary school teachers.